Changing representations of organized crime in the Italian press - Ronco, Anna Di (Trends in organized crime, 2018)
Organized crime has long captured the attention of media, with books, movies, television, and the press offering different representations of what organized crime is. These representations tend to vary in different countries according to the specific coverage and reporting preferences of local media. The ways in which organized crime is framed by the media is of great importance, as mediated images of organized crime may have powerful effects on both the general public and policy-makers. The narrative presented, however, might be distorted and not fully correspond to the notion of organized crime as framed by academic communities. Particularly in the Italian scenario, scholarly definitions and narratives around organized crime have evolved and have been refined meaningfully over the years, presenting a complex multi-layered, and diversified criminal panorama. Several studies have recently addressed press representations of Italian organized crime in the foreign press. However, the way in which the Italian press has represented the changing rhetoric on organized crime has so far been under-investigated. This research presents the results of a longitudinal media analysis of a selection of Italian newspapers, which aims to inspect the ways in which the press has represented the threats posed by organized crime over time.